2009
DOI: 10.4049/jimmunol.0900649
|View full text |Cite
|
Sign up to set email alerts
|

Src Homology 2-Domain Containing Leukocyte-Specific Phosphoprotein of 76 kDa Is Mandatory for TCR-Mediated Inside-Out Signaling, but Dispensable for CXCR4-Mediated LFA-1 Activation, Adhesion, and Migration of T Cells

Abstract: Engagement of the TCR or of chemokine receptors such as CXCR4 induces adhesion and migration of T cells via so-called inside-out signaling pathways. The molecular processes underlying inside-out signaling events are as yet not completely understood. In this study, we show that TCR- and CXCR4-mediated activation of integrins critically depends on the membrane recruitment of the adhesion- and degranulation-promoting adapter protein (ADAP)/Src kinase-associated phosphoprotein of 55 kDa (SKAP55)/Rap1-interacting a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 59 publications
3
44
1
Order By: Relevance
“…Notably, T cells expressing the Y571F mutant showed comparable levels of adhesion as cells reexpressing wild type ADAP under both stimulation conditions, whereas a significant reduction of adhesion was observed in the absence of endogenous ADAP, as previously reported (Fig. 5B, 5C) (5,39,51). In accordance with published results, PMA bypassed the requirement for ADAP and Mn 2ϩ treatment served as a positive control of the adhesive capacity of these cells.…”
Section: The Adap and Zap70 Interaction Is Inducible In A Cellularsupporting
confidence: 91%
See 3 more Smart Citations
“…Notably, T cells expressing the Y571F mutant showed comparable levels of adhesion as cells reexpressing wild type ADAP under both stimulation conditions, whereas a significant reduction of adhesion was observed in the absence of endogenous ADAP, as previously reported (Fig. 5B, 5C) (5,39,51). In accordance with published results, PMA bypassed the requirement for ADAP and Mn 2ϩ treatment served as a positive control of the adhesive capacity of these cells.…”
Section: The Adap and Zap70 Interaction Is Inducible In A Cellularsupporting
confidence: 91%
“…S5) (49). In contrast to TCR stimulation it was previously shown that this supramolecular assembly is not formed upon chemokine stimulation (39). Thus, the phosphorylation of Y571 of ADAP seems mandatory for the interaction between ADAP and ZAP70 only after CXCR4 stimulation.…”
Section: The Adap and Zap70 Interaction Is Inducible In A Cellularmentioning
confidence: 84%
See 2 more Smart Citations
“…Phosphorylated ADAP binds the SH2 domain of SLP-76 (da Silva et al 1997;Musci et al 1997). This interaction is crucial for adhesion and integrin function in T cells (Baker et al 2009;Horn et al 2009;Wang et al 2009). Tyrosine phosphorylated Shb also binds the SH2 domain of SLP-76 and promotes LAT, SLP-76, Vav, and PLC-g1 phosphorylation (Lindholm et al 1999;Lindholm et al 2002).…”
Section: Molecules Recruited To Lat Via Slp-76 Promote T-cell Activationmentioning
confidence: 99%